2014
DOI: 10.4103/0972-124x.128209
|View full text |Cite
|
Sign up to set email alerts
|

To estimate salivary aspartate aminotransferase levels in chronic gingivitis and chronic periodontitis patients prior to and following non-surgical periodontal therapy: A clinico-biochemical study

Abstract: Context:Saliva can be used as a diagnostic fluid in dentistry. Various enzymes have been proposed as markers for periodontal destruction. One of them is aspartate aminotransferase, for which salivary analysis can offer a cost-effective approach for monitoring the disease. Changes in enzymatic activity reflect metabolic changes in the gingiva and periodontium in inflammation.Aims:The purpose of this study was to assess the aspartate aminotransferase levels in saliva prior to and following scaling and root plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
(38 reference statements)
0
12
1
2
Order By: Relevance
“…Chambers DA. et al [9] published the first study that indicated an increase in the AST levels in gingival fluid in dogs during the experimental periodontitis.Since that time, many researchers have found that the AST activity in the saliva is proportionate to the degree of tissue damage during the chronic periodontitis [10,11] and gingivitis [12]. Due to the pathological process in periodontal tissues, the integrity of the cells is impaired, the permeability of their membranes is disturbed, and thus the AST is increasingly released from the cytoplasm into the saliva.Also, the AST values in the saliva [13] and gingival fluid [14] were in correlation with the values of the CPITN index (Community Periodontal Index of Treatment Needs).…”
Section: Discussionmentioning
confidence: 99%
“…Chambers DA. et al [9] published the first study that indicated an increase in the AST levels in gingival fluid in dogs during the experimental periodontitis.Since that time, many researchers have found that the AST activity in the saliva is proportionate to the degree of tissue damage during the chronic periodontitis [10,11] and gingivitis [12]. Due to the pathological process in periodontal tissues, the integrity of the cells is impaired, the permeability of their membranes is disturbed, and thus the AST is increasingly released from the cytoplasm into the saliva.Also, the AST values in the saliva [13] and gingival fluid [14] were in correlation with the values of the CPITN index (Community Periodontal Index of Treatment Needs).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, periodontal status might be considered a contributing factor for the presence of HCV in saliva [ 61 ]. While the aspartate transaminase (AST) salivary levels have recorded significantly higher levels in samples from patients with chronic periodontal disease and the values of AST correlate to the degree of periodontal tissue injury [ 62 ], viral RNA molecules have been found in saliva samples of HCV patients regardless of their periodontal status [ 63 ].…”
Section: Hcv Infection Transmission: Periodontal Disease and Oral mentioning
confidence: 99%
“…The liver function is mainly evaluated by means of serological testing of two enzymes—aspartate aminotransferase (AST) and alanine aminotransferase (ALT), their levels being elevated in hepatic distress and inflammation. The AST salivary levels have recorded significantly higher levels in samples from patients with chronic periodontal disease as shown in a study by Kudva et al, and what is more, the values of salivary AST correlate to the degree of periodontal tissue injury [ 62 ].…”
Section: Periodontal Disease: Impact On Hcv Infectionmentioning
confidence: 99%
“…The two most common hepatic enzymes, aspartate aminotransferase (AST) and alanine aminotransferase (ALT), used for liver function assessment, can also be assessed in the gingival crevicular fluid and saliva. The level of these enzymes has been shown to fluctuate according to the inflammatory status of the periodontal tissues [86][87][88]. The fact that transaminases recorded a decreased activity subsequent to periodontal treatment suggests that the periodontal inflammation and the aggression caused by periodontal bacteria can have extending effects that exceed the periodontal tissues.…”
Section: Connections Between Hcv Infection and Periodontal Statusmentioning
confidence: 99%